Crystallization kinetics and structure refinement of catio3 glass-ceramics produced by melt-quenching technique - Da Silveira, Wagner [UNESP]; Macedo, Wagner Costa [UNESP]; De Almeida Santos, Gleyson Tadeu [UNESP]; Dos Santos, Luis Fernando [UNESP]; Fernandes, José Diego [UNESP]; De Oliveira Rocha, Kleper [UNESP]; Teixeira, Silvio Rainho [UNESP] (FapUNIFESP (SciELO), 2021)
Glass-ceramic materials were obtained by heat treatment (960°C for 2, 4, and 6 hs) of glasses with CaCO3 47.50 wt%-TiO2 23.75 wt%-SiO2 23.75-Al2O3 5.00 wt% formulation produced by the melt-quenching technique (melting at 1650°C and subsequent annealing at 650°C). The materials' structural characterization and crystallization kinetics (Kissinger method) indicate the presence of CaTiO3, CaSiO3, and CaTiSiO5 crystalline phases with activation energies 217, 281, and 446 kJ/mol, respectively. The structure refinement (Rietveld method) suggests metastability for the CaSiO3 and CaTiSiO5 phases as a function of the heat treatment time. The increase in time favors CaTiO3 crystallization, from 62.97 wt%, in the 2 hs treated sample, to 79.21 wt%, in the 6 hs treated sample. EDS and microstructure analyses confirm the glass-ceramic production and indicate segregation of the CaTiO3 phase for longer heat treatment times.
Keywords: CaTiO3; Glass-ceramics; Kissinger Method; Melt-quenching Technique; Rietveld Method